Pengaruh Faktor Demografis dan Faktor Sosial Terhadap Tingkat Keputusan Pembelian Makanan Tradisional di Pasar Wage Nganjuk - Vyanita Utami; Dwi Rahayu; Ambarwati (Penerbit Jurnal Indonesia, 2025)
The objectives of this study are 1) to determine the influence of demographic factors (age) on the level of decision to purchase traditional foods, 2) to determine the influence of demographic factors (gender) on the level of decision to purchase traditional foods at Wage Market in Nganjuk, 3) to determine the influence of social factors (social class) on the level of decision to purchase traditional foods at Wage Market in Nganjuk, 4) to determine the effect of social factors (income level) on the level of decision to purchase traditional foods at the Wage Nganjuk market. The research method used was a quantitative approach. Data collection techniques were carried out by distributing questionnaires to buyers of traditional foods at the Wage Nganjuk market, using purposive sampling. The sample size was determined using the Lemeshow formula, which produced a minimum size of 96.04 respondents, then rounded up to 100 to anticipate incomplete data. Data analysis was performed using multiple linear regression using the SPSS program. The results showed that partially, the variables of age, gender, social class, and income level had a significant effect on purchasing decisions, with a significance value of < 0.05. Simultaneously, the four variables also had a significant effect with a significance value of 0.000. The Adjusted R Square value of 0.941 indicates that 94.1% of the variation in purchasing decisions can be explained by the independent variables in this study, while the remaining 5.9% is influenced by other factors outside the model.